Iron intake with the risk of breast cancer among Chinese women: a case–control study. Issue 17 (23rd December 2021) - Liu, Kai-Yan; Feng, Xiao-Li; Mo, Xiong-Fei; Lin, Fang-Yu; Zhang, Xin; Huang, Chu-Yi; Abulimiti, Alinuer; Li, Lei; Zhang, Cai-Xia
Abstract: Objective: The current study evaluated the associations between different forms and sources of Fe and breast cancer risk in Southern Chinese women. Design: Case–control study. We collected data on the consumption of Fe from different forms and food sources by using a validated FFQ. Multivariable logistic regression and restricted cubic spline (RCS) analysis was used to reveal potential associations between Fe intake and breast cancer risk. Setting: A case-control study of women at three major hospitals in Guangzhou, China. Participants: From June 2007 to March 2019, 1591 breast cancer cases and 1622 age-matched controls were recruited. Results: In quartile analyses, Fe from plants and Fe from white meat intake were inversely associated with breast cancer risk, with OR of 0·65 (95 % CI 0·47, 0·89, P trend = 0·006) and 0·76 (95 % CI 0·61, 0·96, P trend = 0·014), respectively, comparing the highest with the lowest quartile. No associations were observed between total dietary Fe, heme or non-heme Fe, Fe from meat or red meat and breast cancer risk. RCS analysis demonstrated J-shaped associations between total dietary Fe, non-heme Fe and breast cancer, and reverse L-shaped associations between heme Fe, Fe from meat and Fe from red meat and breast cancer. Conclusion: Fe from plants and white meat were inversely associated with breast cancer risk. Significant non-linear J-shaped associations were found between total dietary Fe, non-heme Fe and breast cancer risk, and reverse L-shaped associations were found between heme Fe, Fe from meat or red meat and breast cancer risk.